Triplex-forming oligonucleotides as an anti-gene technique for cancer therapy - Li, Chun; Zhou, Zunzhen; Ren, Chao; Deng, Yi; Peng, Feng; Wang, Qiongfen; Zhang, Hong; Jiang, Yuan (Frontiers in Pharmacology, 2022)
Triplex-forming oligonucleotides (TFOs) can bind to the major groove of double-stranded DNA with high specificity and affinity and inhibit gene expression. TFOs have gained prominence because of their potential applications in antigene therapy. In particular, the target specificity of TFOs combined with their ability to suppress oncogene expression has driven their development as anti-cancer agents. So far, TFOs have not been used for clinical treatment and seem to be gradually snubbed in recent years. But TFOs still represent an approach to down-regulate the expression of the target gene and a carrier of active substances. Therefore, in the present review, we will introduce the characteristics of TFOs and their anti-cancer research progress. Then, we will discuss the challenges in their application.